Post-circumcision urethrocutaneous fistulae: presentations, repairs and outcomes in a tertiary centre - Jideofor Okechukwu Ugwu; Okechukwu Hyginus Ekwunife; Victor Ifeanyichukwu Modekwe; Timothy Uzoma Mbaeri; Sylvester Okwuchukwu Obiechina; Chuka Abunike Ugwunne (Wolters Kluwer Medknow Publications, 2023)
Background: Circumcision is regarded as the most common surgical procedure world over. It is also perceived to be a simple and safe procedure; however, it could be fraught with major urological complications such as urethrocutaneous fistula (UCF). Repair of these fistulae poses a great reconstructive challenge to the paediatric surgeon/urologist with varied outcomes. Aim: We seek to review the presentations, repair and outcome of post-circumcision UCFs managed in a tertiary centre. Patients and Methods: This is a retrospective review of all the consecutive cases of repaired post-circumcision UCFs in Nnamdi Azikiwe University Teaching Hospital, Nnewi, South-East Nigeria, over a period of 9 years (January 2012-December 2020). Data on demography, size of fistula, type of repair and outcome were retrieved from the Records Department and patients' case notes and were analysed using SPSS (version 22, Chicago, Illinois). Results: A total of 22 boys had post-circumcision UCF repair within the period, and they were aged between 2 weeks and 108 months with a median age of 4 months at presentation and aged between 8 months and 144 months with a median age of 24 months at the time of surgery. Circumcisions were by freehand technique in 21 (95.5%). Nurses performed most of the circumcisions in 19 (86.4%), and most of the circumcisions were performed in private hospitals 7 (31.8%), maternity homes 3 (13.6%) and general hospitals in 10 (45.5%) each, respectively. Most 17 (77.3%) fistulae were coronal, and the size of defect ranged from 1 mm to 10 mm. The most commonly employed technique of repair was simple closure in 16 (72.2%). Meatal stenosis and re-fistulation occurred in 2 (9.1%) and 4 (18.2%), respectively. Only two (12.5%) required reoperation. There was no relationship between the size of defect and re-fistulation, P = 0.377. Conclusion: Majority of the Post-circumcision urethrocutaneous fistulae were from free hand technique of circumcisions . These were performed mostly by nurses in general, private hospitals and maternity homes. Hence, there is a need to ramp up training of providers of neonatal circumcision in our environment. Most UCF in children could be repaired with simple closure technique reinforced with dartos flap.